Politics of Disaster: Earthquake, Rehousing, and Confronting Colonial Rule in Accra (Gold Coast/Ghana), 1939–45 - Bin-Kasim, Waseem-Ahmed (Journal of African history, 2023)
Despite its destructiveness, disaster clears the way to accomplish a set of goals. That was why the Gold Coast governor and officials welcomed the 1939 earthquake as an opportunity to rebuild Accra. However, mishandling their reconstruction plan proved disadvantageous. The aftermath of the disaster, including an unprecedented rehousing project, exacerbated urban discontent. How everyday urban residents responded to rehousing further exposed the weakness of the colonial state and gave momentum to nationalism. The paper introduces natural disasters and relief programs into the scholarly narratives that have demonstrated that anticolonial nationalism emerged from a chain of grievances from amongst colonial subjects, some of which were unfulfilled social and economic expectations. The experiences of rehousing following the earthquake powerfully informed local perspectives and contributed to the chain of events leading to formal decolonization.